(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to analyze the effect of awareness of paying taxes, knowledge and understanding of tax regulations, tax sanctions and motivation on taxpayer compliance. The sampling method used a questionnaire in order to obtain 42 respondents who live in Bantul, Yogyakarta. The analytical method used in this research is multiple regression analysis method. The results showed that the tax sanctions variable had a significant positive effect on taxpayer compliance. While the variables of awareness of paying taxes, knowledge and understanding of tax regulations and motivation have no effect on tax compliance.